2018
DOI: 10.1111/ases.12681
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in thoracoscopic esophagectomy for esophageal cancer

Abstract: Technical advances and developments in endoscopic equipment and thoracoscopic surgery have increased the popularity of minimally invasive esophagectomy (MIE). However, there is currently no established scientific evidence supporting the use of MIE as an alternative to open esophagectomy (OE). To date, a number of single‐institution studies and several meta‐analyses have demonstrated acceptable short‐term outcomes of thoracoscopic esophagectomy for esophageal cancer, and we recently reported one of the largest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 77 publications
(134 reference statements)
0
33
0
2
Order By: Relevance
“…However, several problems still have not been solved. First, short-term outcomes were not obviously improved in esophageal cancer patients undergoing MIE [10]. Second, the oncological results of MIE remain to be proven, as no RCTs have demonstrated the long-term survival between MIE and OTE [11].…”
Section: Introductionmentioning
confidence: 99%
“…However, several problems still have not been solved. First, short-term outcomes were not obviously improved in esophageal cancer patients undergoing MIE [10]. Second, the oncological results of MIE remain to be proven, as no RCTs have demonstrated the long-term survival between MIE and OTE [11].…”
Section: Introductionmentioning
confidence: 99%
“…High complication rates, longer recovery times, and the desire for a less invasive procedure is what led to the innovation driving minimally invasive surgery. Specifically for esophagectomy, the definition of a MIE includes varying thoracoscopic and laparoscopic approaches for esophageal resection based on the location of the tumor, clinical stage, and patient characteristics [20,21] . In 1991, Dallemagne et al [22] first reported the use of laparoscopy for a hiatal hernia repair, inspiring Cuschieri et al [23,24] who utilized thoracoscopy for esophagectomy in 1992.…”
Section: Minimally Invasive Techniquesmentioning
confidence: 99%
“…There are two different approaches to abdominal laparoscopy: hand‐assisted laparoscopic surgery (HALS), which provides the advantage of gentle gastric mobilization, and laparoscopic surgery (LAP), which allows easy lymph node dissection around the celiac artery. Although the efficacy of thoracoscopic esophagectomy has recently been clarified, the usefulness of laparoscopy has yet to be investigated 3,4 . Moreover, the differences in postoperative morbidity, mortality, and survival between HALS and LAP remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Although the efficacy of thoracoscopic esophagectomy has recently been clarified, the usefulness of laparoscopy has yet to be investigated. 3,4 Moreover, the differences in postoperative morbidity, mortality, and survival between HALS and LAP remain unclear. Therefore, we aimed to examine and compare the safety and feasibility of HALS and LAP in esophagectomy in patients with esophageal cancer.…”
Section: Introductionmentioning
confidence: 99%